2000
DOI: 10.1063/1.126583
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties of (111)A GaAs/AlGaAs multiquantum-well structures grown by metalorganic vapor phase epitaxy

Abstract: We present the heterointerfacial properties of GaAs/AlGaAs multiquantum-well structures grown by atmospheric-pressure metalorganic vapor phase epitaxy on (111)A GaAs substrates at a relatively low growth temperature of 600 °C. For a 25-period GaAs/Al0.27Ga0.73As multiquantum-well structure with a well width of 44 Å, a photoluminescence linewidth of 10.5 meV was observed, which is smaller than previously reported for a similar GaAs/AlGaAs multiquantum-well structure grown by molecular beam epitaxy on (111)A GaA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The corresponding full widths at half maximum ͑FWHMs͒ of these PL signals are 6.3, 8.4, and 11.8 meV, respectively. Because of simultaneous growth, the QW widths are different, as observed by other authors 27,28 and also in our samples ͑see Table I͒, with the smallest value for wells grown along the ͓311͔B direction. As a result, one might expect that the PL peak of this sample shifts to higher energies when compared to those of the others.…”
Section: Fig 1 Hrxrd Experimental Profile and Theoretical Best Fit supporting
confidence: 76%
“…The corresponding full widths at half maximum ͑FWHMs͒ of these PL signals are 6.3, 8.4, and 11.8 meV, respectively. Because of simultaneous growth, the QW widths are different, as observed by other authors 27,28 and also in our samples ͑see Table I͒, with the smallest value for wells grown along the ͓311͔B direction. As a result, one might expect that the PL peak of this sample shifts to higher energies when compared to those of the others.…”
Section: Fig 1 Hrxrd Experimental Profile and Theoretical Best Fit supporting
confidence: 76%
“…Previously, Chin et al reported a FWHM of 13.4 meV for a five-period MQW grown on a (111)A GaAs substrate by MBE with a well width of 100 Å. 26 Sanz-Hervás et al 10 reported a FWHM of 10.5 meV for a similar structure ͑25-period GaAs/Al x Ga 1Ϫx As MQW͒ with a narrower well width (L w ϭ44 Å). A FWHM of 12.5 meV for sample MQ25 is therefore among the best values reported for GaAs/Al x Ga 1Ϫx As MQWs grown on (111)A GaAs substrates either by MBE or MOVPE.…”
Section: E Evaluation Of Interface Roughness and Well-width Fluctuatmentioning
confidence: 99%
“…7 We previously reported the successful growth of high quality GaAs/AlGaAs QW structures on (111)A GaAs substrates by MOVPE using a relatively low substrate temperature ͑600°C͒. [7][8][9] In a recent letter 10 we presented a preliminary comparison of the interfacial properties of GaAs/Al x Ga 1Ϫx As 25-period multi-QW ͑MQW͒ structures simultaneously grown on (111)A and ͑100͒ GaAs substrates by MOVPE. However, to the best of our knowledge, there has been no report on a comprehensive analysis of the interfacial properties of the (111)A GaAs/Al x Ga 1Ϫx As material system.…”
Section: Introductionmentioning
confidence: 99%